Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
Immunostimulants were widely used in aquafeed due to their multiple important functions, including promoting growth, enhancing non‐specific defence mechanisms and resisting infectious diseases. But the efficiencies of the positive effects of immunostimulants were affected by the duration of the administration and their dose. Short‐term and normal‐dose of immunostimulants promoted the growth and enhance non‐specific immunity of aquatic animals. However, improper use led to several immune disorders, including immune tolerance, immune exhaustion and over‐immunity. The application of two immunostimulant diets in rotation technique and the intermittent use of immune stimulant diets may solve the problems associated with immune disorders, but this application method will be limited by both species and immunostimulants. The occurrence of immune disorders is accompanied by different degrees of gut microbiota dysbiosis, especially significantly up‐regulated the abundance of Proteobacteria. Besides, the gut symbiotic microbiota plays a significant role in host immunity. Consequently, the regulation of gut microbiota may be an effective way to modulate immune disorders caused by improper use of polysaccharide immunostimulants. Regulating the gut microbiota not only solves the negative effects caused by improper use of immunostimulants without restrictions on both species and immunostimulants, but also has the advantage of simplicity and convenience compared to conventional approaches. In summary, this article reviews the possible negative effects caused by improper use of immunostimulants on aquatic animals and compares regular approaches with regulating gut microbiota. And gut microbiota maybe be used as a therapeutic target to improve immune disorders caused by immunostimulants in aquatic animals.